PHARMACOGENOMICS AND REGULATION OF APOPTOSIS IN ACUTE MYELOID LEUKAEMIA: MINI REVIEW - Pravdić, Zlatko; Suvajdžić-Vuković, Nada (Medicinski podmladak, 2020)
Acute myeloid leukaemia (AML) is a heterogenous clonal hematopoietic malignancy primarily treated with combination of cytarabine (ara-C) and anthracyclines. Despite high remission rates, especially in younger patients a vast majority of patients die due to relapse or chemotherapy/stem cell transplantation-related toxicity. The partial explanation for this grim clinical outcomelies in the patients¢ genetic variability. In this review we summarize how genetic polymorphisms of proteins in metabolic paths of cytarabine and anthracyclines and proteins involved in regulation of apoptosis influence efficacy and toxicity in the AML treatment.